2021
DOI: 10.1177/11297298211060964
|View full text |Cite
|
Sign up to set email alerts
|

Single-centre experience with endovascular rotational thrombectomy for single session salvage of thrombosed arteriovenous fistulas and grafts

Abstract: Objectives: This paper documents our experience and outcomes of using a relatively new endovascular rotational thrombectomy device for salvage of thrombosed vascular access. Methodology: A retrospective study reviewing patients with thrombosed native AVF or AVG who underwent endovascular declotting using a rotational thrombectomy device between November 2018 and May 2020 at a tertiary university hospital in Southeast Asia. We evaluated demographics, procedural data, technical and procedural success, patency ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Additionally, no bleeding, infection, or vein breakage was found in our study, which indicated the safety of our technology. In contrast, perioperative complications have been reported in the literature to be 0% to 7% with other thrombectomy methods [14,22,23].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, no bleeding, infection, or vein breakage was found in our study, which indicated the safety of our technology. In contrast, perioperative complications have been reported in the literature to be 0% to 7% with other thrombectomy methods [14,22,23].…”
Section: Plos Onementioning
confidence: 99%